Formulation and Evaluation of Floating Stomach Specific In Situ Gel of Nizatidine - Pawar, Akash Singh (International Journal of Pharmaceutical & Biological Archive, 2014)
Formulation and Evaluation of Floating Stomach Specific In Situ Gel of Nizatidine